L‐Glutamate stimulates cholecystokinin secretion via the T1R1/T1R3 mediated PLC/TRPM5 transduction pathway. (1st July 2020) - Kang, Cuicui; Wang, Lvyang; Feng, Jiangyin; Zhu, Weiyun; Hang, Suqin
Abstract: BACKGROUND: It is known that cholecystokinin (CCK) plays an essential role in reducing food intake and driving weight loss. Previous studies demonstrated that amino acids were capable of triggering CCK release through G protein‐coupled receptors, but the sensing mechanism remains obscure, especially the intracellular signaling pathway. RESULTS: l ‐Glu, rather than its d ‐isomer, robustly stimulated CCK secretion in a porcine duodenal model, and the secretory response was augmented by incubation with the allosteric ligand of T1R1, while T1R3 antagonist attenuated it. Upon inhibiting phospholipase C (PLC) or transient receptor potential M5 (TRPM5) activity, l‐ Glu failed to increase CCK release. Oral administration of monosodium glutamate in rats also suppressed food intake and increased plasma CCK levels, accompanied by elevated expression of T1R1, PLCβ2 and TRPM5 in the duodenum. CONCLUSION: These data demonstrated that l‐ Glu stimulated CCK secretion through the activation of T1R1/T1R3 in a PLC/TRPM5‐dependent manner. © 2020 Society of Chemical Industry